The influence of corporate governance and human governance towards corporate financial crime in Malaysia / Wan Nailah Abdullah - Abdullah, Wan Nailah (2018)
Corporate financial crime (CFC) incidences happen every single year in listed companies of Bursa Malaysia, regardless of various recognitions received for exemplary practices of corporate governance (CG) standard. CFC involving listed companies can be traced down through the Securities Commission's criminal cases and various reports in the mass-media. The ineffectiveness of CG mechanisms in curbing this crime has been proposed in this study as being due to the inappropriateness of CG as "corporate mechanisms" to be used as means for controlling the behaviour of human-being behind the organization. The study, hence, proposes the significance of human governance (HG) factors to be explored, in investigating their effectiveness in mitigating CFC. HG has been used to address the issue of CG's failure as a controlling mechanism, suggesting that there should be needs to concentrate on people, as in the study i.e., directors and top management teams, in formulating the governance regulations. Motivated by lack of studies in CFC in Malaysia and empirical evidence in the area of HG, the study is significance to the literature through the inclusion of HG factors in the area of CFC. Using educational background and previous job experiences of directors and top management teams (TMT) as proxies to HG, the study postulates that organizations with higher HG are expected to be free from CFC incidences. In addition, the study also seeks to investigate the effectiveness of internal and external governance in relation to CFC incidences to find out whether CG roles are still relevantly effective in the current situation. Theoretical contributions include 1) providing empirical evidence of HG concept; 2) adding more studies lacking in CFC in Malaysia; 3) inclusion of Religious Education, Business Education, Military and Police and separate Risk Management Committee variables in relationship with CFC incidences; 4) testing the theory originally used in "street crime" i.e., Social Control Theory, and management's Agency Theory in the study of CFC. Practical contributions include 1) providing empirical evidence in the recruitment criteria for human resource management; 2)as additional information in providing value added standards, rules or regulations by authorities, legislators or governments in the efforts of combatting corporate malfeasance. CFC categories are used to search for crime cases from 2002 until 2014 disclosed from internet, Lexis-Nexis and Securities Commission. 41 crime companies matched with 82 non-crime companies (case control matching ratio 1:2) have resulted into 123 observations. Data for HG, internal and external governance are derived from annual reports of the 123 samples. Logistics regressions results reveal two HG variables: Business Education; and Military and Police job experience indicate significant positive and negative relationship respectively, with CFC incidences. Separate Risk Management Committee (internal governance), Ownership Concentration and Foreign Corporation Ownership (external governance) indicate significant negative, positive and positive relationship respectively, with CFC incidences. Upper Echelon Theory, Social Control Theory and Agency Theory are found to be effective in postulating CFC incidences. The study concludes HG as effective mechanisms in preventing CFC and should be importantly considered besides the conventional CG mechanisms. It is also concluded in the study that internal and external governance are still relevant as effective mechanisms in combating CFC incidences.